Inbetween the Worlds – Gastarbeiter Novel Taxi Driver of Munich: An Anthropological Analysis - Ana Banić Grubišić (University of Belgrade, 2020)
From the perspective of the anthropology of migrations and literature, the paper analyzes The Taxi Driver of München, a novel with autobiographical elements by the Croatian author and gastarbeiter Romano Mrkić. After outlining the basic genre characteristics of "migrant literature" and the so-called gastarbeiter novel, the paper proceeds to analyze the dominant themes and motifs in the novel The Taxi Driver of München. This work, written in the tradition of realist narration, deals with the immediate experience of migranthood and represents a prototype of the first-generation gastarbeiter novel. It is narrated from the perspective of a "guest worker" in Germany – through the character of the protagonist, the taxi driver Marko Mandić, Romano Mrkić writes about himself and his immigrant experience, about important Others and the complex modalities of migrant identity and (non)belonging. In addition to depicting the everyday experience of the gastarbeiter in Germany and their struggle to integrate into a new and different social environment, and describing the native population's ethnic prejudice and stereotypes in relation to the guest workers, Mrkić speaks from an insider perspective of "Yugo-Germans'" "adversities" of identity. His characters remain perpetually stuck between "two worlds", between "here" and "there", and between the past and the present, while the "myth of return" expressed through an overemphatic nostalgia for the homeland is the foundation of Mrkić's narrative. Through a thematic analysis of the novel, the paper explores the ideas of integration and assimilation of guest workers, as well as the cultural meanings that the author assigns to these processes.